Competitive strategies for Chinese mushroom export to the Japanese market - Sun, Haiwei (SLU/Dept. of Economics, 2010)
China is a major country for mushroom production and its export targets the Asian and Japanese markets in particular. The Japanese vegetable import amounted to $ 2.21 billion and mushrooms were the leading imports, comprising 14 to 18 percent of the total value of Japanese vegetable imports (Dyck & Ito, 2001, p64). The high consumption attracts exporters around the world. More than 10 kinds of imported mushrooms can be found, besides the domestic and the Chinese. In the Japanese market by the year 2000, Chinese mushrooms had a great price advantage. The low price strategy adopted by the Chinese mushroom exporters was able to win market access and approval by the Japanase consumers. After the year 2006, Japan began to increase its trade protectionism which led to a decrease in the price advantage of many exports in its domestic market.